Effects of blood flow restriction training on aerobic capacity and performance in endurance athletes: a systematic review and meta-analysis - ZekaiZhang, Zhang; XuejiaoGao, Gao; LangGao, Gao (BioMed Central, 2025)
Background: Although blood flow restriction (BFR) training has been increasingly investigated for its potential to enhance aerobic capacity and performance in endurance athletes, its overall effectiveness remains inconclusive. This systematic review and meta-analysis aimed to evaluate the impact of BFR training on aerobic capacity, muscle strength, and endurance performance in endurance athletes compared to the same training without BFR. Methodology: Databases searched included PubMed, Scopus, Web of Science, and SPORTDiscus through September 2024. The methodological quality of the included studies was assessed using the PEDro tool, with meta-analyses conducted using the R program. Results: A total of 20 studies, involving 407 subjects, were included in the meta-analysis. The results revealed that BFR training had moderate effects on improving VO2max (ES = 0.465, 95% CI [0.222, 0.707], P < 0.001)) and endurance performance (ES = 0.693, 95% CI [0.252, 1.135], P < 0.01). Additionally, it demonstrated a large effect on maximal strength (ES = 1.022, 95% CI [0.267, 1.778], P < 0.01) and a small effect on aerobic power (ES = 0.315, 95% CI [0.015, 0.616], P < 0.05). Furthermore, subgroup analyses showed that age, athlete level, training duration, frequency, type, and cuff pressure did not significantly moderate the effectiveness of BFR training. Conclusions: BFR training significantly enhances aerobic capacity, muscle strength, and overall performance in endurance athletes compared to similar training without BFR. This approach provides a practical strategy for improving endurance and strength, especially during periods when high-intensity training is less feasible, such as recovery phases or in-season maintenance. The prospero registration number: CRD42024581910.